Managing corporate reputation,stakeholder relations and corporate social responsibility : a Southeast Asian perspective - Abdullah, Zulhamri; Abdul Aziz, Yuhanis (2011)
The purpose of this paper is to identify the importance of and relationships between the three key concepts of corporate reputations and corporate social responsibility from a managerial perspective of corporate communication and corporate marketing. Despite the significant alignment and integration between corporate reputation, stakeholder relations and corporate social responsibility in their practice, all these have been managed as business duties (regulated), not genuinely for the substantial contribution to a larger social community and environment (self-regulated).